Precursor designs for Cu2ZnSn(S, Se)4 thin-film solar cells. (May 2017) - Yang, Kee-Jeong; Sim, Jun-Hyoung; Son, Dae-Ho; Kim, Young-Ill; Kim, Dae-Hwan; Nam, Dahyun; Cheong, Hyeonsik; Kim, SeongYeon; Kim, JunHo; Kang, Jin-Kyu
Abstract: To commercialize Cu2 ZnSn(S, Se)4 (CZTSSe) thin-film solar cells, it is necessary to improve their efficiency and to develop the technological ability to produce large-area modules. Defect formation due to the secondary phase is considered to be one of the main reasons for decreased CZTSSe thin-film solar-cell efficiency. This study explores the potential capabilities of large-area thin-film solar cells by controlling the defect formation using various CZTSSe precursor designs, and by improving the characteristic uniformity within the thin-film solar cells. Alloying the precursor as a stack of discrete layers can result in lateral segregation of elements into stable-phase islands, yielding a non-uniform composition on small length scales. It is found that the application of an indiscrete layer by minimizing the precursor-layer thickness allows avoiding Zn rich inhomogeneities in the absorber that would favor formation of detrimental ZnS-ZnSe secondary phases and deep defects. Among the various precursor layers designed by considering the reaction mechanism under annealing, a sample with 15 precursor layers is found to exhibit a shallow electron-acceptor energy level, high photovoltaic conversion efficiency, and uniform characteristics over the corresponding thin-film solar cell. Based on such improvements in both the efficiency and characteristic distribution, it is expected that the commercialization of CZTSSe thin-film solar cells can be advanced. Graphical abstract: An indiscrete layer was chosen as a precursor stacking order design, which enabled the suppression of the overly rich Zn zone during a relatively low-temperature annealing process, thus preventing the formation of Zn-rich detrimental secondary phases and defects in these regions. A higher PCE and a uniform composition ratio distribution, which helped to realize uniform characteristics across the solar cell, were obtained. Highlights: An indiscrete layer enabled the suppression of the overly rich Zn zone. It prevents the formation of Zn-rich detrimental secondary phases and defects. A sample with 15 precursor layers exhibits a shallow acceptor energy level.